Factor that influencing employee engagement at Syarikat Air Johor (SAJ) Sdn Bhd, Segamat Agency / Nurfarahin Sanip - Sanip, Nurfarahin (Faculty of Business and Management, 2015)
Employee engagement has emerged as a critical driver of business success in today’s competitive marketplace. Further, employee engagement can be a deciding factor in organizational success. Not only does engagement have potential to significantly affect employee retention, productivity and loyalty, it is also a key link to the customer satisfaction, company reputation and overall stakeholder value. Engaging employees is necessary to make them fall in line with the mission, goals, and values of the organization and also to facilitate in setting issues and concerns between the employer and the employees. This study intends to see the factors that may influenced employee engagement at the Syarikat Air Johor (SAJ) Sdn. Bhd, Segamat Agency. This study was included four factors which is work environment, leadership, training and career development and compensation and benefits. In order to collect data to analyse, a quantitative method was employed and data were collected by distributing 127 questionnaires to all employees at Syarikat Air Johor (SAJ) Sdn Bhd, Segamat Agency. The data were analysing using Statistical Package for Social Science (SPSS 2.0 Version) to get the Descriptive Analysis, Pearson Correlation Analysis and Regression Analysis. The result showed that there is a relationship between employee engagement with factors of work environment, leadership, and training and career development, when the significant level is below 0.05. The result also revealed that work environment is the factor that most influenced the employee engagement, followed by leadership, training and career development. In conclusion, it shows that when the work environment was comfortable and secure for employee tends to more engaged to the companys.